2007
DOI: 10.1177/0002716207305951
|View full text |Cite
|
Sign up to set email alerts
|

The Political Consequences of Perceived Threat and Felt Insecurity

Abstract: The authors draw on data from a national random digit dial (RDD) telephone sample of 1,549 adult Americans conducted between October 15, 2001, and March 2, 2002, to explore the impact of a need for security on support for national security policies in the aftermath of the 9/11 terrorist attacks. They examine support for protective government policies among individuals who vary in their ability to feel secure in the aftermath of terrorism, exploring the interaction between perceived threat and felt security. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 52 publications
(61 reference statements)
8
102
1
1
Order By: Relevance
“…First, the violence carried by the rival provides clear-cut evidence about its inhumane character and its mal-intentions (5). Second, living in fear and uncertainty can increase group polarization and extremism (6)(7)(8). Third, examining scaled-up interventions in field studies poses methodological constraints on implementing a successful intervention and designing rigorous research to assess the interventions' effectiveness (e.g., refs.…”
mentioning
confidence: 99%
“…First, the violence carried by the rival provides clear-cut evidence about its inhumane character and its mal-intentions (5). Second, living in fear and uncertainty can increase group polarization and extremism (6)(7)(8). Third, examining scaled-up interventions in field studies poses methodological constraints on implementing a successful intervention and designing rigorous research to assess the interventions' effectiveness (e.g., refs.…”
mentioning
confidence: 99%
“…Consistent with this idea, Huddy et al (2007) found that felt security was influenced by factors other than perceived threat, and feeling insecure interacted with perceived threat to predict aggressive post-9/11 foreign policies. Because the security condition in this experiment was added for methodological rather than theoretical reasons, I did not have specific hypotheses about the impact of security cues.…”
Section: Discussionmentioning
confidence: 66%
“…For instance, national threats predict public support for domestic security policies and aggressive foreign policy, including preemptive wars (e.g., Carnagey & Anderson, 2007;Herrmann, Tetlock, & Visser, 1999;Huddy, Feldman, & Weber, 2007). In the aftermath of 9/11 attacks, the U.S. government devised a color-coded warning system to alert American people about the level of threat facing their country.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly little work has been done on grievance as 25 I have relied a great deal on the extensive work of Leonie Huddy et al (2007) in this field, which directly explores threat and its connection to emotion. Surprisingly little work has been done on grievance as 25 I have relied a great deal on the extensive work of Leonie Huddy et al (2007) in this field, which directly explores threat and its connection to emotion.…”
Section: Transgression/grievancementioning
confidence: 99%